Mau‘iẓat al-Ikhwān and the Knowledge of the Acehnese Past - Hadi, Amirul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This article attempts to study a work of late nineteenth century Aceh, known as Mau‘iẓat al-Ikhwān. The main bulk of this inquiry revolves around the question of how far the text conveys the ‘historical knowledge’ of Aceh at the height of its war against the Dutch within the time of its composition (1886 AD). The work, which is a short treatise with only 14 pages in length, was written by Shaykh Muḥammad ‘Abbās al-Āshī, a prominent ‘ālim (religious scholar) and a war leader. Its composition was initially intended as an ‘exhortation’ (mau‘iẓat) for the Acehnese in their efforts at waging the holy war against the Dutch, and therefore it was addressed to them for contemporary use. Yet, as a product of the past the text also encompasses some factual data which can enrich our knowledge of the Acehnese past, especially that of the late nineteenth century. As such, the work plays its role beyond its initial intention as it also functions as a historical source. This study employs a ‘descriptive analytical’ method which will be supported by the mode of Culler’s ‘hermeneutics of recovery’.